Effects of the Single Market programme on foreign direct investment into developing countries. - AGARWAL, Jamuna Prasad (1994)
Discusses the extent to which the fears of developing countries regarding investment diversion to Greece, Portugal and Spain can be justified on theoretical grounds. Argues that much foreign direct investment, such as in natural resources and services, is location specific, or aimed at supplying the domestic markets of host countries, thus FDI flows from developed to developing countries would be largely unaffected by the Single Market programme.